2017
DOI: 10.3390/ijms18081779
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cell Growth of Adipocyte-Derived Mesenchymal Stem Cells Using Chemically-Defined Serum-Free Media

Abstract: The multipotency and anti-inflammatory effects of mesenchymal stem cells (MSCs) make them attractive for cell therapy in regenerative medicine. A large number of MSCs is required for efficient therapy owing to the low homing efficiency of MSCs to target sites. Furthermore, owing to limitations in obtaining sufficient amounts of MSCs, in vitro expansion of MSCs that preserves their differentiation and proliferative potential is essential. The animal factor included in culture media also limits clinical applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 50 publications
6
32
0
Order By: Relevance
“…hBMSCs isolated and cultured in XFS showed a higher and more stable proliferation rate than FBS-hBMSCs, suggesting that the XFS culture can enable the efficient production of therapeutic cells in a shorter time. These data are consistent with those reported for adipose-derived MSCs and human dental pulp stem cells cultured in chemically defined xenofree media (Lee et al, 2017;Mochizuki and Nakahara, 2018). The maintenance of the typical MSC-phenotype according to the ISCT criteria (Dominici et al, 2006) underpins the use of this XFS culture system for MSC isolation.…”
Section: Discussionsupporting
confidence: 88%
“…hBMSCs isolated and cultured in XFS showed a higher and more stable proliferation rate than FBS-hBMSCs, suggesting that the XFS culture can enable the efficient production of therapeutic cells in a shorter time. These data are consistent with those reported for adipose-derived MSCs and human dental pulp stem cells cultured in chemically defined xenofree media (Lee et al, 2017;Mochizuki and Nakahara, 2018). The maintenance of the typical MSC-phenotype according to the ISCT criteria (Dominici et al, 2006) underpins the use of this XFS culture system for MSC isolation.…”
Section: Discussionsupporting
confidence: 88%
“…As an alternative, human serum or human platelet lysate can be used for MSCs' expansion (Mannello and Tonti, 2007;Bieback, 2013;Hemeda et al, 2014). Chemically defined xeno-free media could provide acceptable cell growth and elimination of the risk of carrying over pathogens (Spees et al, 2004), but the evaluation of functional characteristics of the cells cultivated in such media has to be improved (Lee et al, 2017).…”
Section: Media Composition: Basal Medium and Supplementsmentioning
confidence: 99%
“…Ideally, a suitable FBS substitute should present defined composition, reduced risk of contamination, low costs, easy availability, and extended shelf life [ 73 ]. Some studies have reported the use of a stirred tank bioreactor for MSC expansion under xenogeneic- (xeno-) free conditions with the use of human serum [ 39 ] and chemically defined culture medium [ 74 , 75 ]. The first FDA approved commercial xeno-free culture medium was StemPro MSC SFM (Invitrogen).…”
Section: Msc Manufacturing: From Conventional Cultures To Bioreactmentioning
confidence: 99%